2014
DOI: 10.1002/ca.22382
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical evidence for an endocrine activity of the vomeronasal organ in humans

Abstract: The mammalian vomeronasal organ (VNO) is a well-adjusted chemosensory structure that facilitates social and reproductive behavior in mammals. The existence, locality, and function of this organ in human adults remain a matter of discussion. Most authors now agree that a neuroreceptive function of the adult human VNO can be excluded due to the absence of both neural receptive cells associated with the VNO in other mammals despite the enigmatic reports on the effects of pheromones on human behavior. Adult cadave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In mice, for example, some pheromone receptors may also be present in the main olfactory epithelium (Omura and Mombaerts 2014;Kanageswaran et al 2015), possibly explaining why some apparently pheromone-mediated behavior is maintained in species lacking the vomeronasal organ. Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011). Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011).…”
Section: Vomeronasal Lossmentioning
confidence: 99%
“…In mice, for example, some pheromone receptors may also be present in the main olfactory epithelium (Omura and Mombaerts 2014;Kanageswaran et al 2015), possibly explaining why some apparently pheromone-mediated behavior is maintained in species lacking the vomeronasal organ. Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011). Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011).…”
Section: Vomeronasal Lossmentioning
confidence: 99%
“…The adult human VNO possesses a number of features similar to that of the fetal VNE and that of non-human vertebrates, although it appears to have lost its sensory capacity (57, 10). However, in adult humans, there are a number of connections of VNO cells with the underlying capillaries, indicating that the VNO has evolved to take on a more endocrine function (11). Although the role of VNO with respect to peptide uptake in humans is equivocal, the actions of the main olfactory epithelium are less so.…”
Section: Peptides and The Blood Brain Barriersmentioning
confidence: 99%
“…Functional aspects of the human VNO are a subject of debate, because no accessory olfactory bulbs which receive information from the vomeronasal receptor cells are present (D'Aniello et al 2017). Wessels et al (2014) reported that the VNO has an endocrine function (rich capillary bed underlying VNO cells and secretion of calcium-binding protein).…”
Section: Vomeronasal Organmentioning
confidence: 99%